2021
DOI: 10.1177/17488958211051513
|View full text |Cite
|
Sign up to set email alerts
|

Street gangs and coercive control: The gendered exploitation of young women and girls in county lines

Abstract: This article explores young women and girls’ participation in gangs and ‘county lines’ drug sales. Qualitative interviews and focus groups with criminal justice and social service professionals found that women and girls in gangs often are judged according to androcentric, stereotypical norms that deny gender-specific risks of exploitation. Gangs capitalise on the relative ‘invisibility’ of young women to advance their economic interests in county lines and stay below police radar. The research shows gangs mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 72 publications
2
18
0
Order By: Relevance
“…The money that comes with CLG work is undoubtedly a huge driving factor for young people’s associations. However, practitioners suggested that while the initial money looks tempting to an impoverished young person, once enticed they are hugely exploited and in some instances, entrapped with the use of debt bondage (Havard et al , 2021). This happens when a young person is purposefully set up to be robbed by the gang that they are supplying drugs for, only then to be forced to work off the cost of the lost goods, plus interest.…”
Section: Discussionmentioning
confidence: 99%
“…The money that comes with CLG work is undoubtedly a huge driving factor for young people’s associations. However, practitioners suggested that while the initial money looks tempting to an impoverished young person, once enticed they are hugely exploited and in some instances, entrapped with the use of debt bondage (Havard et al , 2021). This happens when a young person is purposefully set up to be robbed by the gang that they are supplying drugs for, only then to be forced to work off the cost of the lost goods, plus interest.…”
Section: Discussionmentioning
confidence: 99%
“…Victim-survivors may be in relationships with men who, because of their associations with other men, are extremely powerful and well-resourced. These women are facing coercion not just from one abusive man but from patriarchal collectives of men (Havard et al, 2023) that may even permeate the systems of law enforcement.…”
Section: Entrapment: Including the Broader Social Contextmentioning
confidence: 99%
“…In comparison to male gang members, female gang members are known to display higher rates of delinquency (Deuchar et al 2020;Peterson et al 2001). This may be a product of females falling victim to peer influence (Deuchar et al 2020) or the threat of abuse or victimization (Harding 2014;Havard et al 2021).…”
Section: Gender Differences and Gangsmentioning
confidence: 99%